Development of techniques for capillary chromatography of terpene hydrocarbons and oxygenated components of essential oils - Фролова, Наталия Эпинетовна; Усатюк, Елена Михайловна (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis of existing techniques for chromatographic study of essential oils has shown that under the same chromatography conditions of terpenes and their oxygenated derivatives, poor separation of peaks in the chromatogram, their imposition or masking of one peaks by some other is observed. The paper presents the study of the conditions of the gas chromatographic analysis of essential oils on capillary columns with a maximum separation of terpene hydrocarbons and oxygenated components. When developing techniques, stationary phases were chosen, gas-carrier and its rate, heating temperatures of columns, detector, injector were selected. According to the results of experiments, Carbowax 20M capillary column with a polar stationary phase was used in the separation technique of oxygenated aromatic components of essential oils. For the separation of terpene hydrocarbons, a column with a nonpolar stationary phase - HP-5MS (crossliness 5 % PHME siloxane) FilmThickness: 0,25 mm, lenght 30 m, phaseratio 250, column ID 0,25 mm was used in the technique. Both techniques are characterized by high separation efficiency of the essential oil components and allow to determine their quantitative ratios with the total error į=15 %, with p=0,95. The developed techniques can be implemented on the flame ionization detector chromatograph, contain all the necessary data to study the composition of essential oils of both essential oil plants and aromatic plants of the new selection.